What Drives Refugees' Return After Conflict? - Joop Age Harm Adema; Lasha Chargaziia; Yvonne Giesing; Sarah Necker; Panu Poutvaara (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Refugees' decisions to return after conflict carry significant political and economic implications for the origin and host countries. We examine how conflict resolution, security, economic conditions, and corruption influence return decisions. To estimate the causal effect of post-war conditions, we conducted a single-profile conjoint experiment among 2543 Ukrainian refugees across 30 European countries. Respondents were asked how likely they would be to return to Ukraine under different hypothetical scenarios. Results show that territorial integrity and security guarantees are critical, while economic prospects and combating corruption also play an important role. Refugees planning to return are more responsive to different post-war scenarios, and younger respondents are particularly influenced by income opportunities, job prospects, and potential EU accession. Our findings suggest that targeted political and economic reconstruction policies can substantially influence post-conflict return. In the most optimistic scenario, the expected return rate is 47%; in the most pessimistic scenario, only 3%.
Keywords: F22; D74; O15; 330; refugees; return migration; conflict; integration; Ukraine; conjoint experiment